Customers’ satisfaction towards institutional foodservices : an insight into universities in the Klang Valley, Malaysia. - Othman, Mohhidin; Salehuddin, Nadzirah; Abdul Karim, Mohd. Shahrim; Ghazali, Hazrina (World Business Institute, 2013)
As one of Southeast Asia’s centers for educational tourism, many tertiary institutions in Malaysia are tryinghard to offer its captive populace with quality on - site foodservice. Apart from meeting customers’ daily dietary needs, these providers are also obligated to comply with the university’s stipulation in providing acceptable quality of food and service at their on- campus cafeterias and restaurants. To date, there is no published empirical evidence showing the current state of customer satisfaction towards Malaysian institutional foodservice incorporating more than one university. Therefore, the aim of this study is to evaluate determinants influencing customer satisfaction of institutional foodservice at 25 universities in one of Malaysia’s highly developed boroughs: the Klang Valley. This study was carried out from September to December 2011, with its sample frame being students and staff from Klang Valley’s selected tertiary institutions. A SERVQUAL - type questionnaire was developed based on items determined by an initial Profile Accumulation Technique(PAT) survey and previous literature. A total of 2162 usable questionnaires were collected. The data was analyzed using frequency, factor analysis, t - test, gap analysis and multiple regression analysis. This study found that most customers have negative disconfirmations with their foodservice establishments, which point toward on - campus foodservice for not meeting with customers’ expectations. Findings denote customers’ preference of buying food off - campus, despite the fact that majority indicated that they would always purchase from on - campus foodservice facilities. Further evidence had revealed that there is a strong relationship between Customer Perception and Customer Satisfaction, specifying determinants such as ‘Products Quality’, ‘Value to Customer’ and ‘Technological Application’ have significant effect on Customer Satisfaction. This study will contribute to better understanding of determinants which affect customer perception and expectation, and the insights will specifically help Malaysia’s institutional foodservice providers to minimize the occurrence of service failures, improve recovery efforts, increase customer satisfaction, and generate positive repatronage behavior.